Narratives of women residing in a rural area on intimate partner violence: a case of Chimanimani District, Eastern Highlands (Zimbabwe) - Chadambuka, Cyndirela (My University, 2021)
This study explored the phenomenon of intimate partner violence (IPV) in rural areas in Zimbabwe. Similar to other countries, IPV remains a serious social problem in Zimbabwe that affects the psychosocial wellbeing of women. Regardless of its detrimental effects, IPV is largely unexplored in rural areas and this makes it difficult to establish its extent and interventions required. In addition, the IPV interventions that are crafted do not effectively respond to the needs of women in rural communities. Thus, this study explored the IPV experiences of women residing in a rural area in Zimbabwe. This study utilised a qualitative research approach. Document analysis was used when reviewing literature. Narrative research design guided the study. Purposive sampling was utilised to recruit participants from one ward in Chimanimani Rural District in Zimbabwe. The participants in this study were categorized into two groups. The first group consisted of women who had experienced IPV in their previous intimate relationships, had exited abusive relationships and were not facing on-going IPV. These women were also chosen on the grounds of their residency in Chimanimani Rural district and their ages (between 19 and 49 years). The second group consisted of key informants who were key IPV service providers in Chimanimani Rural District. In-depth interviews using a narrative approach were adopted as the main method of data collection. The in-depth interviews were guided by semi-structured interview schedules with open-ended questions. The interviews were audio-recorded with participants’ permission. Thematic analysis was used to analyse data. Together with previous literature reviewed, the findings from this study revealed that women living in rural areas experience frequent and severe IPV, which is largely unreported due to social norms. It was evident in the findings that social norms play a central role in the perpetration and response to IPV. Viewed from the intersectional feminism perspective, the study findings show that to better understand the experiences of women in rural areas about IPV, the interconnectedness of different social variables such as geographical location, gender and social norms that facilitate the abuse ought to be considered. It emerged in this study that women living in rural areas resort to context-specific coping strategies in responding to IPV. IPV victims in rural areas choose coping strategies that are aligned with social norms (i.e. acceptance and placating) to avoid community rejection and stigma. The study findings further reveal that when these context-specific coping strategies fail, victims of IPV in rural areas resort to informal support systems for support. These informal support networks are family, traditional leaders, church and informal self-help groups (ISGHs) which are readily available and are culturally approved. However, in the case of life-threatening IPV, formal support systems play an important role in the provision of the needed support and intervention. The study findings revealed the barriers that IPV victims in rural areas face in seeking help from formal support systems and these barriers include lack of confidentiality and strained intervention resources. Notable in this study are the challenges that IPV service providers in rural areas face such as lack of intervention resources and limited male participation and conflicting identities. These challenges affected service providers’ ability to intervene effectively in IPV situations in rural areas. Utilizing the findings from this research, this study proposes culture-informed practice guidelines for social workers working within IPV contexts in rural areas. These guidelines look at intervention from the lens of intersectional feminism arguing that intervention efforts should be sensitive to the unique experiences of women residing in rural areas and prevention efforts should take into consideration the intersection of social norms, geographical location and gender in drafting intervention strategies. The conclusions reached in this study are that, firstly, social norms are central to IPV perpetration and the responses to it in rural areas. Secondly, culture and religion commonly determine the coping strategies that women living in rural areas employ in managing and responding to IPV. Thirdly, IPV victims in rural areas are reliant on informal support networks because they are readily available and are deemed culturally appropriate in resolving marital conflicts. Fourthly, service provision in rural areas is tied to cultural norms and this affects the effectiveness of intervention efforts. Understanding the scope of IPV and the role of social norms in its perpetration and response is crucial in social work practice as it allows practitioners to contribute to the development of IPV and gender policies and implement programmes that are culturally sensitive and which respond to the unique needs of IPV victims in rural areas
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in the Department of Social Work, Faculty of Humanities at the University of the Witwatersrand, 2021